2021
DOI: 10.1038/s41408-021-00440-4
|View full text |Cite
|
Sign up to set email alerts
|

Relapsed multiple myeloma demonstrates distinct patterns of immune microenvironment and malignant cell-mediated immunosuppression

Abstract: Immunotherapy has shown efficacy in relapsed multiple myeloma (MM). However, these therapies may depend on a functional tumor immune microenvironment (iTME) for their efficacy. Characterizing the evolution of the iTME over the disease course is necessary to optimize the timing of immunotherapies. We performed mass cytometry, cytokine analysis, and RNA sequencing on bone marrow samples from 39 (13 newly diagnosed [NDMM], 11 relapsed pre-daratumumab exposure [RMM], and 13 triple-refractory [TRMM]) MM patients. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…CD4 T cells play a critical role in developing and sustaining effective antitumor immunity and are crucial in orchestrating the immune response through activation and maintenance of cytotoxic CD8 T cells, secretion of Eff cytokines, and direct cytotoxicity against tumor cells. 35 Recent studies in MM have shown that CD4 T cells elicit effective anti-MM responses 36,37 and that decreased CD4 T-cell counts are associated with adverse prognosis and diminished treatment responses, 28,38,39 highlighting an important functional role of CD4 T cells.…”
Section: Discussionmentioning
confidence: 99%
“…CD4 T cells play a critical role in developing and sustaining effective antitumor immunity and are crucial in orchestrating the immune response through activation and maintenance of cytotoxic CD8 T cells, secretion of Eff cytokines, and direct cytotoxicity against tumor cells. 35 Recent studies in MM have shown that CD4 T cells elicit effective anti-MM responses 36,37 and that decreased CD4 T-cell counts are associated with adverse prognosis and diminished treatment responses, 28,38,39 highlighting an important functional role of CD4 T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have showed dynamic interaction of myeloma cells with the surrounding tumor microenvironment in a mutually pro-survival fashion [15][16][17] . The tumor microenvironmental network promotes myeloma cell growth, survival, proliferation, drug resistance and angiogenesis by affecting various epigenetic and genetic molecular events, including miRNA alterations.…”
Section: Discussionmentioning
confidence: 99%
“…The relapse status we referred not to healthy donors but to the MRD-negative status, which, from our point of view, is closest to the actual condition of the BM microenvironment of patients after effective treatment and which is modulated in the disease-progression process. In turn, more heavily pretreated patients have highly proliferative malignant clones that downregulate pathways required for tumor immunosurveillance [40], which limits the reliability of relating our data to healthy individuals.…”
Section: Discussionmentioning
confidence: 99%